Peran Jurnalistik dan Kehumasan Digital Akun Youtube Agak Laen dalam Meningkatkan Antusiasme Penonton - Wandra Adhira; Muhammad Yoserizal Saragih (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This article explores the role of digital journalism through public relations strategies in increasing audience enthusiasm for the film Agak Laen via the Agak Laen Official YouTube channel. The urgency of this study lies in the importance of understanding how digital communication and public relations approaches can shape emotional engagement, expand promotional reach, and build audience communities in the era of social media. This research employs a qualitative method using a case study approach. Data were collected through in-depth interviews with eight informants, participatory observation, and digital content documentation. The findings reveal that promotional content such as behind-the-scenes footage, podcasts, use of local dialects, and actor involvement foster emotional closeness and audience participation. The discussion is grounded in the Diffusion of Innovations theory and Viral Marketing, showing that authentic and emotional digital strategies accelerate film adoption and trigger viral effects through social interaction. The YouTube channel serves not only as a promotional medium but also as a participatory communication agent that shapes positive perceptions and loyalty toward the film. In conclusion, the synergy of local narratives, consistent content, and digital interactivity forms a new, effective promotional model in Indonesia's digital film industry, serving as a strategic reference for contemporary film communication management.